Vitamin D deficiency is common in psychogeriatric patients, independent of diagnosis - Grønli, Ole Kristian; Kvamme, Jan-Magnus; Jorde, Rolf; Wynn, Rolf (BMC Psychiatry, 2014)
This article is part of Ole Kristian Grønli's doctoral thesis which is available in Munin at http://hdl.handle.net/10037/6930 Background:Previous studies have found an association between psychiatric disorders and vitamin D deficiency, but most studies have focused on depression. This study aimed to establish the prevalence of vitamin D deficiency in elderly patients with a wider range of psychiatric diagnoses. Method: The study included elderly patients (>64 years) referred to a psychiatric hospital in Northern Norway and a control group from a population survey in the same area. An assessment of psychiatric and cognitive symptoms and diagnoses was conducted using the Montgomery and Aasberg Depression Rating Scale, the Cornell Scale for Depression in Dementia, the Mini Mental State Examination, the Clockdrawing Test, and the Mini International Neuropsychiatric Interview (MINI+), as well as clinical interviews and a review of medical records. The patients’ mean level of 25-hydroxyvitamin D (25(OH)D) and the prevalence of vitamin D deficiency were compared with those of a control group, and a comparison of vitamin D deficiency across different diagnostic groups was also made. Vitamin D deficiency was defined as 25(OH)D <50 nmol/L (<20 ng/ml). Results: The mean levels of 25(OH)D in the patient group (n = 95) and the control group (n = 104) were 40.5 nmol/L and 65.9 nmol/L (p < 0.001), respectively. A high prevalence of vitamin D deficiency was found in the patient group compared with the control group (71.6% and 20.0%, respectively; p < 0.001). After adjusting for age, gender, season, body mass index, and smoking, vitamin D deficiency was still associated with patient status (OR: 12.95, CI (95%): 6.03-27.83, p < 0.001). No significant differences in the prevalence of vitamin D deficiency were found between patients with different categories of psychiatric diagnoses, such as depression, bipolar disorders, psychosis, and dementia. Conclusion: Vitamin D deficiency is very common among ...